The Glasgow prognostic score: Useful information when prescribing palliative radiotherapy - Nieder, Carsten (Mol Clin Oncol, 2017)
The purpose of the present retrospective study was to investigate whether a score reflecting systemic inflammatory processes [the Glasgow Prognostic Score (GPS)] provides relevant information for radiation oncologists. GPS is a three-tiered score [0: normal C-reactive protein (CRP) and albumin; 1: one abnormal result; 2: increased CRP and low albumin]. Correlations between disease type and extent, resource utilization, survival and GPS were analyzed in 703 patients. In the subgroup with GPS 2, significantly higher rates of lung, adrenal gland and liver metastases were observed. An increasing GPS score was associated with a higher likelihood of anemia, leukocytosis and thrombocytosis. Comparable findings were made regarding utilization of palliative care resources, need for blood transfusion and intravenous administration of antibiotics. Compared with GPS 0 or 1, more patients with GPS 2 did not complete their prescribed course of radiotherapy. One-third of patients with GPS 2 received treatment during the final month of life. Multivariate analysis demonstrated that GPS was a significant prognostic factor for overall survival (median, 479, 136, and 61 days, for GPS 0, 1 and 2, respectively). In patients with GPS 2 and additional leukocytosis, the median survival was 38 days. In conclusion, GPS provides important prognostic information. This biomarker-based score may be considered for deciding fractionation, and should be validated further.